Immunoliposomes as an emerging nanocarrier for breast cancer therapy. (7th February 2023) - Parveen, Neha; Abourehab, Mohammed A.S.; Shukla, Rahul; Thanikachalam, Punniyakoti Veeraveedu; Jain, Gaurav Kumar; Kesharwani, Prashant
Graphical abstract: Abstract: The most prevalent non-cutaneous carcinoma in women and the second most prevalent tumour-related condition is breast cancer. There are significant therapeutic choices for treating breast cancer, and all come with adverse reactions. Innovative nanotechnologies showed promise for treating or focusing on breast cancer. Novel nanocarriers for the transport of chemotherapeutics were introduced by developments in protein engineering which completely changed nanomedicine. Recent research has focused on developing components that concurrently include drugs and targeting the site of illness. This article complements existing reviews on liposomal drug delivery by emphasising immunoliposome tumour targeting and summarising numerous experiments of immunoliposome assessment in vivo and in vitro with regard to therapeutic potential, structural liposomal parameters, and the needs of the target sites. Immunoliposomes have been suggested as a promising therapeutic delivery device for the therapy of breast cancer. In this review, we highlight current developments of immunoliposome formulation that synergistically demonstrate distinct target-cell associations while combining or loading with a variety of cytotoxic drugs.